2018
DOI: 10.1002/mnfr.201700729
|View full text |Cite
|
Sign up to set email alerts
|

Mice Fed a High‐Cholesterol Diet Supplemented with Quercetin‐3‐Glucoside Show Attenuated Hyperlipidemia and Hyperinsulinemia Associated with Differential Regulation of PCSK9 and LDLR in their Liver and Pancreas

Abstract: In mice, dietary Q3G could counter HCD-induced hyperlipidemia and hyperinsulinemia, in part by oppositely modulating hepatic and pancreatic PCSK9 secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 59 publications
2
26
2
Order By: Relevance
“…Additionally, Q3G is reported to be as effective as quercetin in ameliorating insulin resistance by regulating the insulin receptor substrate 1 (IRS-1) function of the endothelium [43]. Isoquercetin, otherwise known as quercetin-O-beta-glucoside, is supplemented to a high cholesterol diet that could regulate expression and secretion of proprotein convertase subtilisin/kexin type 9 (PCSK9), reversing the hyperlipidemia and hyperinsulinemia caused by the diet [44]. In accordance with the previous and present works, these studies have shown that cooperatively the antioxidant and anti-diabetic effects of LSE may be attributed to their biological activities of the flavonoids components.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Q3G is reported to be as effective as quercetin in ameliorating insulin resistance by regulating the insulin receptor substrate 1 (IRS-1) function of the endothelium [43]. Isoquercetin, otherwise known as quercetin-O-beta-glucoside, is supplemented to a high cholesterol diet that could regulate expression and secretion of proprotein convertase subtilisin/kexin type 9 (PCSK9), reversing the hyperlipidemia and hyperinsulinemia caused by the diet [44]. In accordance with the previous and present works, these studies have shown that cooperatively the antioxidant and anti-diabetic effects of LSE may be attributed to their biological activities of the flavonoids components.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin-3-glucoside, a glucoside form of quercetin, can alleviate hyperlipidemia and hyperinsulinemia in mice fed a high-cholesterol diet (Mbikay et al, 2018). Moreover, quercetin contributes to alleviating male reproductive toxicity caused by environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The target miRNAs of circRNA_0049392 are miR-7037-5p and miR-6919-5p, which have been validated as a receptor of low-density lipoprotein (LDL). LDL receptor encoded by Ldlr gene allows the degradation of LDL [15]. A study conducted by Kelli et al, in 2017 [16] have re ected the attenuated disease development, decreased triglycerides accumulation and decreased in ammation responses in Ldlr-/mice fed with HFD.…”
Section: Discussionmentioning
confidence: 99%